Determinants of customer satisfaction and return visit interest in culinary tourism in Bandung - Putra Maulana; Elistia Elistia (Indonesia Accounting Research Journal, 2025)
Culinary tourism is a key part of tourist behavior, especially when experiencing local food. Braga in Bandung, West Java, is one of Indonesia’s culinary tourism attractions. This study analyzes the determinant factors of customer satisfaction and revisit intention, focusing on food quality, price fairness, and physical environment. A quantitative method employing a descriptive-causal approach was utilized, with data gathered from 220 respondents via an online survey. The analysis, conducted using Structural Equation Modeling (SEM), reveals that food quality has a positive influence on both customer satisfaction and revisit intention. However, price fairness and physical environment do not significantly influence either variable. Additionally, customer satisfaction does not significantly affect revisit intention or mediate the effects of price fairness and physical environment. These findings suggest that food quality is the primary factor influencing satisfaction and repeat visits in Braga's culinary tourism. Visitors prioritize food quality over pricing and environment when evaluating their experiences.